Long term changes in the ionosphere over Indian low latitudes: Impact of greenhouse gases. (June 2015) - Sharma, Som; Chandra, H.; Beig, G.
Abstract: Increased concentration of greenhouse gases due to anthropogenic activities warm the troposphere and have a cooling effect in the middle and upper atmosphere. Ionospheric densities and heights are affected due to cooling. Carbon dioxide is one of the most dominant gases for the cause of long term ionospheric trends along with other radiatively active greenhouse gases. Regular ionospheric soundings are made over Ahmedabad (23.1°N, 72.7°E), since 1953. Long term changes in the ionosphere as a consequence of the cooling of the mesosphere and thermosphere due to the increased concentration of greenhouse gases have been studied. Ionospheric observations over Ahmedabad, a low latitude station in the anomaly crest region, for the years 1955–2003 are examined to study the long term changes in the critical frequencies of the various ionospheric layers and the height of the maximum ionization as characterized by hP F2 . A decrease in fo F2 (1.9 MHz for midday, 1.4 MHz for midnight) and hP F2 (18 km for midday, 17 km for midnight) during about five decades are noted. An increase is noted in fo F1 (0.4 MHz). The fo F2 data are also examined over an equatorial station Kodaikanal (10.2°N, 77.5°E), situated near the magnetic equator for the years 1960–1995 and a decrease of 0.5 MHz for midday and 0.7 MHz for midnight are noted in ~35 years. Highlights: Long term ionospheric trends estimated over Indian low latitudes. Decreasing trend in the F2 layer critical frequencies is found. Height of the F2-region of the ionosphere shows decreasing trend.